Type 1 autoimmune pancreatitis: case scenario and review of the disease - Donet, Jean A. (2016)
Autoimmune pancreatitis (AIP) is an uncommon disease that represents a diagnostic challenge unless it is considered as a cause of acute pancreatitis, pancreatic exocrine insufficiency and a pancreatic mass. This entity is under diagnosed and successful medical therapy is available. In this paper, we will describe a case of a 59 year-old, Hispanic woman diagnosed with autoimmune pancreatitis, a disease previously believed to affect typically older men. We will review the definition, types, clinical manifestations, radiological features, serology, histopathological findings, treatment strategies and diagnostic criteria of autoimmune pancreatitis.